Adjuvant chemotherapy in patients with invasive lobular carcinoma and use of the 21‐gene recurrence score: A National Cancer Database analysis. Issue 9 (9th February 2022) - Weiser, Roi; Polychronopoulou, Efstathia; Hatch, Sandra S.; Haque, Waqar; Ghani, Hafiz A.; He, Jing; Kuo, Yong‐fang; Gradishar, William J.; Klimberg, V. Suzanne
Abstract : Background: Invasive lobular carcinoma (ILC) is traditionally considered less responsive to chemotherapy. Although the Oncotype recurrence score (RS) has been validated to identify high‐risk patients who benefit from chemotherapy, some studies have questioned its relevance in patients with ILC. The objective of this study was to better characterize potential use of the RS in these patients. Methods: The National Cancer Database was used to identify women with stage I through III, T1 through T3, N0 or N1, hormone receptor‐positive, HER2‐negative ILC or invasive ductal carcinoma (IDC) who had an available RS between 2010 and 2016. Multivariable Cox regression was used to model the effect of variables on 5‐year overall survival (OS). The Kaplan‐Meier method was used to estimate OS according to the RS, nodal status, and chemotherapy. Results: In total, 15, 763 patients with ILC and 100, 070 with IDC were identified. The mean age of patients with ILC and IDC was 59.2 ± 9.1 and 57.2 ± 9.8, respectively. A lower percentage of patients with ILC versus those with IDC had a high RS, defined as >25 (6.6% vs 16.0%; P < .0001). ILC patients with a high RS who had N0 or N1 disease received approximately 10% less chemotherapy compared with similar patients who had IDC. The results indicated that the RS had statistically significant prognostic value for patients with ILC. In addition, an absolute OS advantage was correlated with the receipt of chemotherapy by patients with ILC who had a high RS with N0 or N1 disease. Conclusions: Patients with ILC who have a high RS are treated less often with chemotherapy compared with similar patients who have IDC. Nevertheless, the RS has a prognostic as well as a predictive value in ILC, with an association between OS benefit and chemotherapy receipt in patients who have ILC with a high RS, especially if they have N1 disease. Lay Summary: Invasive lobular carcinoma (ILC) is a subtype of breast cancer comprising about 15% of cases. The Oncotype recurrence score (RS) is a genetic test of breast tumors that helps predict which patients might benefit from chemotherapy. Some have doubted the relevance of the RS for patients with ILC. In this study, the authors show that the RS is relevant for patients who have ILC. The RS has the potential of predicting the risk of recurrence and identifying patients with ILC who might benefit from chemotherapy. Abstract : This retrospective analysis of data from the National Cancer Database demonstrates the prognostic as well as the predictive value of the Oncotype recurrence score in patients with invasive lobular carcinoma. Those who have invasive lobular carcinoma with a high recurrence score have an overall survival advantage when treated with chemotherapy, much like patients who have invasive ductal carcinoma.